Comparing the safety and efficacy of over-the-scope suturing, through-the-scope suturing, and endoscopic hand suturing for closure of GI defects after endoscopic resection: systematic review and meta-analysis - Suresh Kumar, Vishnu Charan; Singh, Sahib; Loganathan, Priyadarshini; Mohan, Babu P.; Aswath, Ganesh; Akbar Khan, Hafiz Muzaffar; Sapkota, Bishnu; Andrawes, Sherif; Inamdar, Sumant; Adler, Douglas G. (Gastrointestinal endoscopy, 2025)
Data comparing the efficacy and safety of OverStitch (Apollo Endosurgery, Marlborough, Mass, USA), X-Tack (Apollo Endosurgery), and endoscopic hand suturing (EHS) for closure of GI defects after endoscopic resection are limited. We conducted a meta-analysis of the available data. Online databases were searched for studies evaluating different closure systems for GI defects. The outcomes of interest were technical success, clinical success, and adverse events. Pooled proportions were calculated. Fifteen studies (4 for EHS, 6 for OverStitch, 4 for X-Tack, and 1 for both OverStitch and X-Tack) were included. The pooled outcomes for EHS were 98% technical success, 96% clinical success, 2% adverse events, 3% bleeding, and 1% perforation; for OverStitch were 93% technical success, 93% clinical success, 6% adverse events, 3% bleeding, and 3% perforation; and for X-Tack were 95% technical success, 94% clinical success, 3% adverse events, 2% bleeding, and 1% perforation. All 3 closure methods showed comparable high technical and clinical success rates. EHS and X-Tack had lower adverse event rates than OverStitch. Future direct comparison studies are needed to corroborate our findings. [Display omitted]